2010
DOI: 10.1038/ismej.2010.91
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and resilience of benthic biofilm communities from a temperate saltmarsh to desiccation and rewetting

Abstract: Periods of desiccation and rewetting are regular, yet stressful events encountered by saltmarsh microbial communities. To examine the resistance and resilience of microbial biofilms to such stresses, sediments from saltmarsh creeks were allowed to desiccate for 23 days, followed by rewetting for 4 days, whereas control sediments were maintained under a natural tidal cycle. In the top 2 mm of the dry sediments, salinity increased steadily from 36 to 231 over 23 days, and returned to seawater salinity on rewetti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 72 publications
1
83
0
1
Order By: Relevance
“…This occurs in the diatom genera Cymbella and Gomphonema, which form stalks or tubes where the cells host. Diatoms are also capable of migrating from superficial to deeper sediments, as another survival strategy (Mckew et al, 2010). However, diatoms do not resist complete drying, and other algal groups showing cells with thick walls, such as Rhodophyta and Phaeophyta, are better able to resist the desiccation.…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 99%
See 1 more Smart Citation
“…This occurs in the diatom genera Cymbella and Gomphonema, which form stalks or tubes where the cells host. Diatoms are also capable of migrating from superficial to deeper sediments, as another survival strategy (Mckew et al, 2010). However, diatoms do not resist complete drying, and other algal groups showing cells with thick walls, such as Rhodophyta and Phaeophyta, are better able to resist the desiccation.…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 99%
“…They suggested that the lower resistance of autotrophs than heterotrophs can be attributed to the physical conditions in the different stream compartments. Sand sediments preserve humid conditions enough for the survival of bacteria (Mckew et al, 2010), but not so much for the algae that are light-limited there. The absence of water directly affects the performance of algal photosynthesis; however, some bacterial groups have the ability to remain active under low humidity conditions.…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 99%
“…Hydrocarbon analytes from crude oil were normalized to the 17␣(H), 21␤(H), C 30 -hopane naturally present in crude oil, and the percent depletion of analytes was calculated as described previously by Venosa et al (47). The use of surrogate solutions of the ASTM D5442 standard (C 12 to C 60 ) and Quebec Ministry Environment PAH mix (6) demonstrated that the variations in the reproducibility of the extraction and quantification of six sediment and water samples were Ϯ10% and Ϯ8%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, the estuary lies near one of the busiest shipping lanes in the world and therefore is susceptible to oil pollution. Owing to the high level of microbial diversity (30), relatively high nutrient concentrations (23), and previous exposure to hydrocarbons by boat traffic, our hypotheses were that biodegradation would be rapid and that these intertidal sediments would house a broad diversity of oildegrading microbes. However, because petroleum hydrocarbons may represent a small fraction of the total organic carbon pool in mudflat sediments (50), it is often difficult to associate subtle changes in the microbial community of sediments with the addition of crude oil, especially when intact sediment cores are used.…”
mentioning
confidence: 99%
“…Effects of desiccation and rewetting were tested in benthic communities, and the results demonstrated changes in terms of functions and the composition of bacteria communities. Some studies show that rewetting increases microbial activity (McKew et al, 2011;Conrad et al, 2014). The goal of this study was to contribute to a better understanding of the desiccation and flooding effects on the cyanobacteria community structure in terms of abundance, diversity and evenness indices in a tropical salt flat environment.…”
Section: Introductionmentioning
confidence: 99%